Review: Komposit rGO-TiO2 dalam Proses Fotokatalisis untuk Menghilangkan Kontaminan Warna pada Air - Fitri, Lara Ismano; Heltina, Desi; Amri, Amun (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2024)
This article explains various synthesis methods for rGO-TiO2 materials and their applications in colored wastewater treatment. The methods discussed include hydrothermal, sol-gel, ultrasonication, wet impregnation, electrospinning, and electrophoresis. Each method has its own advantages: the hydrothermal and sol-gel methods enhance photocatalytic activity through the integration of TiO2 and rGO; ultrasonication and wet impregnation methods are effective in uniquely improving photocatalytic performance; while electrophoresis (EPD) and electrospinning methods excel in forming high-quality coatings and nanofibers that boost photocatalytic activity. The choice of method depends on the specific application and desired material properties. The hydrothermal and sol-gel methods are well-suited for photocatalytic applications, while EPD and electrospinning methods are superior for other applications, such as improving photovoltaic performance.